Detoxification Improves Multidomain Cognitive Dysfunction in High-Dose Benzodiazepine Abusers - Federico, Angela; Lugoboni, Fabio; Mantovani, Elisa; Martini, Alice; Morbioli, Laura; Casari, Rebecca; Faccini, Marco; Tamburin, Stefano (Frontiers in Neuroscience, 2020)
Purpose. High-dose benzodiazepines (BZDs) abuse has been documented to cause multidomain cognitive dysfunction. We explored whether cognitive abnormalities to high-dose BZD abuse might be reversed by detoxification with slow subcutaneous infusion of flumazenil. Methods. We recruited 96 patients consecutively admitted to the Department of Internal Medicine, Addiction Medicine Unit, Verona University Hospital, Italy for detoxification from high-dose BZD dependence. After selection for inclusion and exclusion criteria, 50 patients (23 men, 27 women; age 42.7±10.3 years) were included. They underwent a comprehensive neuropsychological battery to explore verbal memory, visuospatial memory, working memory, attention, and executive functions 28-30 days prior to admission for detoxification (T0) and at the end of detoxification, i.e., 7 days after admission (T1). A group of 50 healthy adults (24 men, 26 women; mean age 44.5±12.8 years) matched for age, sex, and education served as controls. Results. At T0, patients scored significantly worse than healthy controls in all the neuropsychological tests. Depression and anxiety scores were associated with impaired verbal memory at T0 in patients. T1-T0 comparison showed improved performances in all neuropsychological tests after the end of detoxification in patients. Conclusion. We confirmed that all neuropsychological domains were significantly and profoundly impaired by high-dose BZD abuse and documented that cognitive abnormalities improved after detoxification with slow subcutaneous infusion of flumazenil.